Abnormal cardiovascular reflexes in patients with gastro-oesophageal reflux. Issue 1 (January 1989) - Chakraborty, T K; Ogilvie, A L; Heading, R C; Ewing, D J
Abstract : Using five non-invasive tests, abnormalities of cardiovascular reflex function were found in 20 of 50 patients with gastro-oesophageal reflux. Abnormalities of pupil cycle time, an index of non-vagal parasympathetic function, were found in only a few patients, implying that the cardiovascular abnormalities observed were not part of a generalised parasympathetic defect. The findings are consistent with the hypothesis that an abnormality of vagal function may contribute to the pathogenesis of gastro-oesophageal reflux.